A decentralized employee performance appraisal framework for recruitment, performance prediction and ranking using permissioned Blockchain and ensemble learning - Anjum, Afra Antara; Islam, Sadaath; Majumder, Shaikat (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.